2015
DOI: 10.5539/jms.v5n3p17
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CSR on Brand Relevant Aspects

Abstract: Companies employ various methods to fulfill their corporate social responsibility (CSR) in order to make a better impression on consumers and play the part of an upstanding world citizen. An important issue is how companies can bring their efforts to the attention of consumers, placing themselves in a more positive light and thereby attracting business.Using a well-known global corporation, McDonalds, as an example, we explored consumer awareness of CSR through literature review and empirical research by consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The present study illustrates that brand trust mediates on its own and, in subsequence with competitive advantage, the relationship between CSR and buying intention. This finding of the current research supports the results of other studies [50] that found that once consumers trust a brand, they repurchase from it, but also recommend it to others; or the study of [13], who emphasized the mediating role of brand trust and brand image with the strong positive effect of CSR on purchase intentions.…”
Section: Csr Initiatives and Buying Intentionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study illustrates that brand trust mediates on its own and, in subsequence with competitive advantage, the relationship between CSR and buying intention. This finding of the current research supports the results of other studies [50] that found that once consumers trust a brand, they repurchase from it, but also recommend it to others; or the study of [13], who emphasized the mediating role of brand trust and brand image with the strong positive effect of CSR on purchase intentions.…”
Section: Csr Initiatives and Buying Intentionsupporting
confidence: 89%
“…One classical definition notes that trust takes place when one party is confident in the exchange partner's reliability and integrity [49]. Brand trust, therefore, refers to the fact that "consumers are willing to believe in and rely on the brand in question" [50].…”
Section: Csr and Brand Trustmentioning
confidence: 99%
“…Moreover, CSR has proven to be an effective source of product differentiation and a tool to meet the needs and concerns of targeted consumer groups (Costanigro, Deselnicu, and McFadden ; De Magistris, Del Giudice, and Verneau ). These consumers tend to identify with companies' products and brands through an identification process (also known as C–C identification) that leads them to choose products that are closer to their values (Bhattacharya and Sen ; Wu and Chen ). Consequently, companies will experience several benefits in terms of brand loyalty, a long‐term relationship (Lee et al ), and a premium price (De Pelsmacker, Driesen, and Rayp ) for these products.…”
Section: Discussionmentioning
confidence: 99%
“…Such ethical management is fostered by media pressure from consumers and NGOs, where companies, in order to protect their reputations, agree to sustainable procurement. In managing a sustainable strategy oriented toward CSR in fisheries, to be truly competitive, it must act as a distinctive marketing lever (Weber, 2009) which should be adequately communicated, affecting reputation, perception, and formation of consent, the process of selection and purchase of a product/service (Christensen, Morsing, & Cheney, 2008; Invernizzi & Romenti, 2011; Siano, Siglioccolo, & Vollero, 2015) and on the brand, as can be seen in the study by Wu and Chen (2015). The addition of sustainability, in its three economic, social, environmental dimensions, into the communication plan of a fishery is a fundamental part of success, for the purpose of customer loyalty (Di Talia, Simeone, & Scarpato, 2019) also benefiting from positive exposure to public relations and the conquering of new target markets.…”
Section: Theoretical Backgroundmentioning
confidence: 99%